The Smart Factory and Its Risks - Frank Herrmann (Systems, 2018)
In this paper, the risks of a Smart Factory are to be examined and structured in order to be able to evaluate the status of the Smart Factory. This thesis thus serves as an overview of the technical components of a Smart Factory and the associated risks. The study takes a holistic view of the smart factory. The results show that the greatest need for action lies in the technological field. Thus, the topics of standardization, information security, availability of IT infrastructure, availability of fast internet and complex systems were prioritized. The organizational and financial risks, which also play an important role in a Smart Factory transformation, are addressed.